Emission dispatch problem with cubic function considering transmission loss using particle swarm optimization - Mahdi, F.P. (Universiti Teknikal Malaysia Melaka, 2016)
In this research, authors have exploited particle swarm optimization (PSO) technique for solving the emission dispatch problem. Authors have used cubic function, instead of quadratic function, to solve emission dispatch problem to make the system more robust against nonlinearities of actual power generator. PSO with cubic function reveals better results by optimizing less emission of hazardous gases, transmission losses and showing robustness against nonlinearities than simplified direct search method (SDSM).